2021
DOI: 10.1371/journal.ppat.1009383
|View full text |Cite
|
Sign up to set email alerts
|

Inactivated rabies virus vectored SARS-CoV-2 vaccine prevents disease in a Syrian hamster model

Abstract: Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) is an emergent coronavirus that has caused a worldwide pandemic. Although human disease is often asymptomatic, some develop severe illnesses such as pneumonia, respiratory failure, and death. There is an urgent need for a vaccine to prevent its rapid spread as asymptomatic infections accounting for up to 40% of transmission events. Here we further evaluated an inactivated rabies vectored SARS-CoV-2 S1 vaccine CORAVAX in a Syrian hamster model. CORAVA… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 48 publications
0
20
0
Order By: Relevance
“…Infected hamsters had a high viral load in the upper respiratory tract but also developed more lower respiratory disease than standard laboratory mice, and they support efficient transmission of SARS-CoV-2, are easier to handle than ferrets (which do not develop moderate respiratory disease and less susceptible in transmission studies), and are considerably less expensive with fewer ethical concerns than nonhuman primates. 9 , 10 , 13 , 14 , 17 , 20 , 28 , 33 , 40 , 43 , 53 Recent publications used hamster models for SARS-CoV-2 vaccine development, and these have included the use of a number of backbones or vectors, including rabies, 22 measles, 25 Newcastle disease, 48 yellow fever, 42 monoclonal antibodies, 2 , 23 , 24 , 44 and nanobodies. 29 , 51 The hamster model has also been used to study new therapeutic agents for the prevention and treatment of infection including favipiravir, 21 hydroxychloroquine, 41 methylprednisone, 52 plant extracts, 34 interferon, 16 remdesivir, 52 anti-leprosy medications, 54 and ranitidiine bismuth citrate.…”
Section: Discussionmentioning
confidence: 99%
“…Infected hamsters had a high viral load in the upper respiratory tract but also developed more lower respiratory disease than standard laboratory mice, and they support efficient transmission of SARS-CoV-2, are easier to handle than ferrets (which do not develop moderate respiratory disease and less susceptible in transmission studies), and are considerably less expensive with fewer ethical concerns than nonhuman primates. 9 , 10 , 13 , 14 , 17 , 20 , 28 , 33 , 40 , 43 , 53 Recent publications used hamster models for SARS-CoV-2 vaccine development, and these have included the use of a number of backbones or vectors, including rabies, 22 measles, 25 Newcastle disease, 48 yellow fever, 42 monoclonal antibodies, 2 , 23 , 24 , 44 and nanobodies. 29 , 51 The hamster model has also been used to study new therapeutic agents for the prevention and treatment of infection including favipiravir, 21 hydroxychloroquine, 41 methylprednisone, 52 plant extracts, 34 interferon, 16 remdesivir, 52 anti-leprosy medications, 54 and ranitidiine bismuth citrate.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, the rabies virus has been successfully used as a vaccine vector for many zoonotic diseases, including Ebola virus (EBOV) disease and COVID-19. Compared with another viral vector, the rabies vaccine vector has an excellent safety profile and impressive immunogenicity profiles in animals and humans (24)(25)(26)(27)(28). Previous studies by us and other research groups have demonstrated that the rabies vector could be desirable for the development of the MERS vaccine.…”
Section: Discussionmentioning
confidence: 99%
“…When rescuing recombinant virus based on RABV vector, the length and form of foreign antigen expression frame as well as its location in the RABV genome would be considered, as these factors have an effect on the expression of target antigen protein and the efficiency of rescued recombinant virus and its virus titer (34). Several studies have demonstrated that the length of inserted exogenous expression frame within 2,000 bp would be ideal (24)(25)(26)(27)(28)(29). Besides, of the two subunits of MERS-CoV spike protein, S1 is the one that contains the RBD and the N-terminal, which are the regions against which more neutralizing antibodies are generated (52).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Vaccinated hamsters showed a reduced or disappeared infectious virus in the lungs and less body weight loss, as well as less histopathological changes of pneumonia. They produced a level of NAbs against SARS-CoV-2 [24][25][26][27]. In short, golden hamsters reflect certain clinical manifestations and immune responses after the administration of COVID-19 vaccines.…”
Section: Golden Hamster Modelsmentioning
confidence: 99%